TINJAUAN UMUM ASPEK HUKUM PENYELESAIAN SENGKETA WILAYAH PERBATASAN NEGARA DALAM RANGKA KETAHANAN NASIONAL - Sumaya, Ira (MEDIA HUKUM, 2014)
According to stipulations of UNCLOS, overcoming the dipute of land areas, could be done by agreements of the states in disputes types to a formal procedure that will issue a binding decission. In the International Relationshio Study, the mecanism of overcoming disputes could be done by 2 (two) methods, they are the non-legal mecanisms, (diplomatic politics) and legal mecanisms. The non-legal mecanisms usually are done by negotiations, medium, good services conciliations. Meanwhile the overcoming through the legal mecanisms usually take the legal process through the courts and arbitary.